An infant with diabetes mellitus: Is it always T1DM?. (March 2017) - Mukherjee, Soham; Rastogi, Ashu; Venkatesan, Radha; Sundaramoorthi, Gopi; Mohan, Viswanathan; Bhansali, Anil
Highlights: Novel heterozygous mutation Arg992Cys in ABCC 8 gene, causing neonatal diabetes in an infant. He was initiated on insulin therapy, but later successfully switched to oral anti-diabetic drug. On follow-up he was found to have permanent form of neonatal diabetes. Abstract: Here we describe a 2 1/2  month old infant with neonatal diabetes mellitus (NDM) who was initially misdiagnosed to have T1DM and initiated on insulin. He was found to have a novel heterozygous mutation Arg992Cys in ABCC 8 gene and successfully switched to oral anti-diabetic drug.